Ayurvedic Herbology and Autism Spectrum Disorder : A Comprehensive Study on Traditional Knowledge, Herbal Pharmacology, and Emerging Clinical Evidence - Dr. Navdeep Sharma (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Autism Spectrum Disorder (ASD) is a multifactorial neurodevelopmental condition characterised by deficits in social communication, restricted behaviours, and frequent co-occurring disturbances such as anxiety, gastrointestinal dysfunction, sleep problems, and immune dysregulation (Lord et al., 2020; Lai et al., 2019). Conventional treatment approaches—including behavioural interventions, educational strategies, and pharmacological management—have improved outcomes but remain limited in addressing core deficits and often carry side effects (Hyman et al., 2020; Zwaigenbaum et al., 2015). This has generated interest in complementary and integrative medicine, particularly Ayurveda, which offers a centuries-old pharmacopeia of botanicals with neuroprotective, adaptogenic, and cognition-enhancing potential (Chaudhary & Singh, 2018). Herbs such as Bacopa monnieri (Brahmi), Withania somnifera (Ashwagandha), Centella asiatica (Gotu kola), and curcumin from Curcuma longa are traditionally used for memory enhancement, stress regulation, and systemic balance, and contemporary pharmacological research demonstrates their roles in modulating oxidative stress, neuroinflammation, mitochondrial dysfunction, and neurotransmitter activity (Stough et al., 2013; Singh et al., 2011; Devkota et al., 2020; Gupta et al., 2021). Emerging clinical and preclinical studies suggest potential behavioural and cognitive benefits in ASD, including improvements in attention, reduction in irritability, and enhanced adaptive functioning, though findings remain preliminary and methodologically heterogeneous (Agarwal et al., 2021; Hurwitz et al., 2021). A key limitation is the lack of large-scale, standardised clinical trials assessing safety, dosage, and herb–drug interactions, which constrains integration into evidence-based practice. This study synthesises traditional Ayurvedic perspectives, mechanistic pharmacology, and current evidence to provide a comprehensive understanding of the relevance of Ayurvedic herbology in ASD. It further highlights research gaps and proposes directions for rigorous, interdisciplinary exploration that may pave the way for safe and effective integrative frameworks in autism care.
Keywords: Social Behaviour; Traditional Ayurvedic Practices; Pharmacology; Herb-Drug Interactions